2014
DOI: 10.2478/nanofab-2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen as a carrier gas for regime control in focused electron beam induced deposition

Abstract: The synthesis of ferromagnetic nanostructures has received great attention over the past few years. These structures are usually manufactured by lithographic structuring of a substrate, blanket deposition of the desired magnetic material and a subsequent lift-off process [1,2]. As a successful alternative to this multi-step procedure, focused electron beam induced deposition (FEBID) allows the mask-and resist-less nanofabrication of planar and three dimensional (3D) structures [3]. In FEBID, the focused electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…In that situation, even for low beam currents such as 21 pA (allowing lateral resolution of 30 nm)Co content greater than 90% is found(60). Similarly, Wachter et al have reported the advantage of Co growth at the crossover between the precursor-limited and electron-limited regimes(82). Summarizing, thermal effects are not necessary to achieve high Co content as thought in the first studies, which makes possible to obtain simultaneously high Co content and lateral resolution.…”
mentioning
confidence: 91%
“…In that situation, even for low beam currents such as 21 pA (allowing lateral resolution of 30 nm)Co content greater than 90% is found(60). Similarly, Wachter et al have reported the advantage of Co growth at the crossover between the precursor-limited and electron-limited regimes(82). Summarizing, thermal effects are not necessary to achieve high Co content as thought in the first studies, which makes possible to obtain simultaneously high Co content and lateral resolution.…”
mentioning
confidence: 91%
“…According to those experiments, the deposited volume increases linearly at low electron current (below approx. 0.5 nA), and the linear growth slows down at higher currents, indicating a transition from the ELR to the PLR [28]. At the same time, a linear increase in the deposit's volume with beam current (indicative of the ELR) has been observed in another FEBID experiment [29] for much higher beam currents up to 22 nA.…”
Section: Introductionmentioning
confidence: 72%
“…The electron-limited and precursor-limited FEBID regimes have been studied theoretically by means of the continuum (diffusion-reaction) models [14,26,27]. Experimentally, these regimes have been identified by measuring the volume variation of the deposits as a function of beam current [28]. According to those experiments, the deposited volume increases linearly at low electron current (below approx.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that for higher beam currents, this transition occurs at higher working pressures, i.e., higher precursor gas fluxes. Thus, the growth rate is determined by the amount of gas molecules delivered (increasing with ΔP), which is known as the precursor-limited regime [ 52 ]. Consequently, the nanowires (or segments of nanowire) grown in the linear regime present a high growth rate, expressed in terms of nanowire’s length per unit of time, while in the radial regime, nanowires grow more slowly.…”
Section: Going 3d: Tuning Febid Growth Parametersmentioning
confidence: 99%